Local Ablative Strategies for Ductal Pancreatic Cancer (Radiofrequency Ablation, Irreversible Electroporation): A Review. (15th February 2016) - Paiella, Salvatore; Salvia, Roberto; Ramera, Marco; Girelli, Roberto; Frigerio, Isabella; Giardino, Alessandro; Allegrini, Valentina; Bassi, Claudio
Abstract : Pancreatic ductal adenocarcinoma (PDAC) has still a dismal prognosis. Locally advanced pancreatic cancer (LAPC) accounts for the 40% of the new diagnoses. Current treatment options are based on chemo- and radiotherapy regimens. Local ablative techniques seem to be the future therapeutic option for stage-III patients with PDAC. Radiofrequency Ablation (RFA) and Irreversible Electroporation (IRE) are actually the most emerging local ablative techniques used on LAPC. Initial clinical studies on the use of these techniques have already demonstrated encouraging results in terms of safety and feasibility. Unfortunately, few studies on their efficacy are currently available. Even though some reports on the overall survival are encouraging, randomized studies are still required to corroborate these findings. This study provides an up-to-date overview and a thematic summary of the current available evidence on the application of RFA and IRE on PDAC, together with a comparison of the two procedures.